Variation in Seed and Fruit Characters of some Commercially Important Agroforestry Species - Thakur, Sanjeev; Sharma, Kamal; Singh, Charan; Gupta, Atul (Indian Forester, 2008)
Aonla, Jamun and Soapnut are the wild fruits/nuts which are important from commercial point of view. The present studies were carried out to assess natural variation in these species in Himachal Pradesh so as to screen out their promising strains for higher and quality production. A wide range of variation was observed in fruit and seed characters of these species which revealed that selection for their improvement could be very effective.